-8.6-3z-8.5-z=-3z+2.3

Simple and best practice solution for -8.6-3z-8.5-z=-3z+2.3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8.6-3z-8.5-z=-3z+2.3 equation:


Simplifying
-8.6 + -3z + -8.5 + -1z = -3z + 2.3

Reorder the terms:
-8.6 + -8.5 + -3z + -1z = -3z + 2.3

Combine like terms: -8.6 + -8.5 = -17.1
-17.1 + -3z + -1z = -3z + 2.3

Combine like terms: -3z + -1z = -4z
-17.1 + -4z = -3z + 2.3

Reorder the terms:
-17.1 + -4z = 2.3 + -3z

Solving
-17.1 + -4z = 2.3 + -3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '3z' to each side of the equation.
-17.1 + -4z + 3z = 2.3 + -3z + 3z

Combine like terms: -4z + 3z = -1z
-17.1 + -1z = 2.3 + -3z + 3z

Combine like terms: -3z + 3z = 0
-17.1 + -1z = 2.3 + 0
-17.1 + -1z = 2.3

Add '17.1' to each side of the equation.
-17.1 + 17.1 + -1z = 2.3 + 17.1

Combine like terms: -17.1 + 17.1 = 0.0
0.0 + -1z = 2.3 + 17.1
-1z = 2.3 + 17.1

Combine like terms: 2.3 + 17.1 = 19.4
-1z = 19.4

Divide each side by '-1'.
z = -19.4

Simplifying
z = -19.4

See similar equations:

| 2(1-x)=3(x+9) | | n+12=n*4 | | 2y+3=7y | | 5(x-7)=2(x+8)+x | | 12-2x+5=-2+(x-3) | | 4(3x-5)-x=-x+16 | | -3m+7=40 | | 3x-2=3x-5+8 | | 4w+6w= | | 3(2x-1)+x=x-3 | | x-10-2x=9 | | 0=x^2-10x+50 | | 5x+5(1-x)=x+8 | | 9x-(4x-3)=11+(2x-2) | | 2x-12=3x-16 | | -3x^3-7x^2-5x+1= | | 19(13a+20)= | | 3x^3-7x^2-5x+1= | | n^2+6n-86=5 | | 12x+3=1232342 | | u^2-8u+16=0 | | 33=-8+4(c-5) | | 35x^3-28x^2=7x | | 4x^2+48=0 | | 5y=8-9y | | 21=-9(8r-3) | | 20x^2-20x^2= | | 4z-9z=6z-3+2 | | 2x+4=2x+16 | | 8x^3+30x^2+18x= | | 4x+5=3x+4 | | 3(2x-7)+7=2(6x+4)+6x-5 |

Equations solver categories